Genetically engineered pigs for xenotransplantation: Hopes and challenges - Xi, Jiahui; Zheng, Wei; Chen, Min; Zou, Qingjian; Tang, Chengcheng; Zhou, Xiaoqing (Frontiers in Cell and Developmental Biology, 2023)
The shortage of donor resources has greatly limited the application of clinical xenotransplantation. As such, genetically engineered pigs are expected to be an ideal organ source for xenotransplantation. Most current studies mainly focus on genetically modifying organs or tissues from donor pigs to reduce or prevent attack by the human immune system. Another potential organ source is interspecies chimeras. In this paper, we reviewed the progress of the genetically engineered pigs from the view of immunologic barriers and strategies, and discussed the possibility and challenges of the interspecies chimeras.